2001
DOI: 10.1016/s0896-6273(01)00273-2
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Diphosphate Kinase, a Source of GTP, Is Required for Dynamin-Dependent Synaptic Vesicle Recycling

Abstract: Nucleoside diphosphate kinase (NDK), an enzyme encoded by the Drosophila abnormal wing discs (awd) or human nm23 tumor suppressor genes, generates nucleoside triphosphates from respective diphosphates. We demonstrate that NDK regulates synaptic vesicle internalization at the stage where function of the dynamin GTPase is required. awd mutations lower the temperature at which behavioral paralysis, synaptic failure, and blocked membrane internalization occur at dynamin-deficient, shi(ts), mutant nerve terminals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 79 publications
6
132
1
1
Order By: Relevance
“…The function of Nme protein as an endocytic factor was noted more than 10 years ago in Drosophila (Dammai et al 2003;Krishnan et al 2001). More recent genetic studies have further supported a more general role in vesicular transport (Feng et al 2014;Hippe et al 2011a;Hippe et al 2011b;Hippe et al 2009).…”
Section: Future Perspectives: a Potential Unifying Themementioning
confidence: 95%
See 1 more Smart Citation
“…The function of Nme protein as an endocytic factor was noted more than 10 years ago in Drosophila (Dammai et al 2003;Krishnan et al 2001). More recent genetic studies have further supported a more general role in vesicular transport (Feng et al 2014;Hippe et al 2011a;Hippe et al 2011b;Hippe et al 2009).…”
Section: Future Perspectives: a Potential Unifying Themementioning
confidence: 95%
“…Early studies in Drosophila showed that awd mutant larval brain exhibited mitotic defects correlated with defective microtubule polymerization (Biggs et al 1990). Subsequently, awd has been implicated in the process of endocytosis in multiple tissues, including neurotransmitter uptake at the neuromuscular junctions (Krishnan et al 2001), surface receptor internalization that modulates the chemotaxis response in tracheal cell and border cell migration (Dammai et al 2003;Nallamothu et al 2008), recycling of adherens junction components (Woolworth et al 2009), and promotion of early-to-late endosome transition that is critical for Notch signaling in follicle cells and in imaginal discs (Ignesti et al 2014). These endocytic functions were associated with the functions of dynamin and Rab5, suggesting a GTP-supplier function for these monomeric GTPases.…”
Section: Drosophila Melanogastermentioning
confidence: 99%
“…Ramaswami's laboratory was interested in identifying genes that regulate neurotransmission at synaptic junctions using forward genetic approaches [40]. In synaptic vesicle recycling and cellular trafficking, endocytosis plays a key role.…”
Section: Awd Regulates Neurotransmission Through Its Endocytic Functionmentioning
confidence: 99%
“…In synaptic vesicle recycling and cellular trafficking, endocytosis plays a key role. Pioneering work in Ramaswami's laboratory revealed that AWD/NM23 is an essential component of endocytosis: AWD was identified as a factor required for dynamindependent synaptic vesicle recycling [40]. Dynamin is a GTPase functioning in a later stage of endocytosis in eukaryotic cells where it pinches off the nascent vesicle by constricting its neck.…”
Section: Awd Regulates Neurotransmission Through Its Endocytic Functionmentioning
confidence: 99%
“…In mammalian tissues, the cytosolic enzyme forms heterohexamers of 17-21 kDa subunits (Gilles et al 1991;Janin et al 2000). These are composed of different combinations of the three major isoforms, NDPK A, B and C. In addition to NTP synthesis, NDPKs are involved in a variety of processes in cellular physiology, including tumour metastasis (Steeg et al 1988), development (Rosengard et al 1989), gene regulation (Postel 2003), apoptosis (Fan et al 2003), endocytosis (Krishnan et al 2001;Palacios et al 2002), vesicular transport from the endoplasmatic reticulum (Kapetanovich et al 2005) and regulation of the cystic fibrosis transmembrane conductance regulator (Crawford et al 2006a).…”
Section: Introductionmentioning
confidence: 99%